The Urgency of Regulating Tax Law for Vehicles After Natural Disasters in Indonesia - Asriyani, Asriyani; Syamsuddin, Adiesty Septhiany Prihatiningsih; Rory, Soleman S (Universitas Negeri Gorontalo, 2021)
The occurrence of a natural disaster on 28 September 2018 in the province of Central Sulawesi Indonesia caused vehicle tax arrears to be incurred by people who were victims of natural disasters. This research is socio-legal research with a statutory and comparative approach to find out the legal arrangements related to tax collection after natural disasters and to compare it with the practices in New South Wales, Australia. This study concluded that there is no specific regulation that differentiates the mechanism of tax collection during normal times and the period after a natural disaster in Indonesia. Local governments are given the authority to regulate it based on the scale of the disaster and the affected areas/people in which people lose their homes and livelihoods so they cannot fulfill their obligations to pay for vehicle tax. This resulted in the arrears of tax collection carried out by the fiscus and become an obstacle for local governments to collect taxes as a source of financing rebuilding infrastructure after a natural disaster. As a comparison, an integrated tax reduction system was applied for disaster victims in New South Wales, including for the vehicle tax. The whole process was done online. Indonesia needs to build such a system to anticipate the bad impact of tax collection that can make disaster victims suffer psychologically.